2020
DOI: 10.1111/2041-210x.13461
|View full text |Cite
|
Sign up to set email alerts
|

Plant and root‐zone water isotopes are difficult to measure, explain, and predict: Some practical recommendations for determining plant water sources

Abstract: 1. Stable isotope ratios of water (δ 18 O, δ 2 H) have long been used to study a core question in plant ecology and ecohydrology: 'From where do plants take up water?' Indeed, decades of research has involved sampling potential plant water sources in the subsurface, classifying those sources as distinct endmembers (e.g. deep vs. shallow soil waters) and then evaluating their contributions to a xylem water sample through mixing-model analysis to identify the depths of root water uptake. 2. However, more detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 119 publications
2
75
0
Order By: Relevance
“…In some cases, these effects can lead to biases and possibly incorrect interpretation of the results even at small scales. Some of these issues have been discussed in recent works (Penna et al, 2018;Barbeta et al, 2019Barbeta et al, , 2020Beyer et al, 2020;Sprenger and Allen, 2020;Von Freyberg et al, 2020) but in this opinion paper we aim at summarizing them in a comprehensive way and stimulating community efforts to address uncertainty in isotope-base studies of vegetation water sources and uncertainty propagation across spatial scales.…”
Section: Heterogeneity and Uncertainty In Isotope-based Estimates Of mentioning
confidence: 99%
“…In some cases, these effects can lead to biases and possibly incorrect interpretation of the results even at small scales. Some of these issues have been discussed in recent works (Penna et al, 2018;Barbeta et al, 2019Barbeta et al, , 2020Beyer et al, 2020;Sprenger and Allen, 2020;Von Freyberg et al, 2020) but in this opinion paper we aim at summarizing them in a comprehensive way and stimulating community efforts to address uncertainty in isotope-base studies of vegetation water sources and uncertainty propagation across spatial scales.…”
Section: Heterogeneity and Uncertainty In Isotope-based Estimates Of mentioning
confidence: 99%
“…Our semi-controlled outdoor pot experiment aimed to minimize potential influences of boundary conditions that typically occur in natural forest environments e.g., soil heterogeneity, subsurface flow and redistribution of soil water, rainfall input, stemflow and associated variability in isotope signatures in the soil-tree compartment (see von Freyberg et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…We argue that the accuracy is well suited to perform tracer labelling experiments and monitor the tracer arrival that is typically orders of magnitude larger than natural isotopic variability. Studies that used destructive sampling also reported variability of isotope measurements taken from one single tree (von Freyberg et al, 2020). This is due to the fact that destructive sampling relies on multiple sampling locations that can differ (naturally) in their isotopic signature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations